Lactate drives cellular DNA repair capacity: Role of lactate and related short-chain fatty acids in cervical cancer chemoresistance and viral infection - Ciszewski, Wojciech M.; Sobierajska, Katarzyna; Stasiak, Anna; Wagner, Waldemar (Frontiers in Cell and Developmental Biology, 2022)
The characteristic feature of a cancer niche is the presence of high concentrations of L-lactate in the tumor-microenvironment. The lactate-rich environment is also maintained by commensal mucosal microbiota, which has great potential for affecting cancer cells through its receptoric and epigenetic mode of action. Some of these lactate activities might be associated with the failure of anticancer therapy as a consequence of the acquisition of a drug resistance by cancer cells. Up-regulation of cellular DNA repair capacity and enhanced drug efflux are the most important cellular mechanisms that account for ineffective radiotherapy and drug-based therapies. Here, we present the recent scientific knowledge on the role of HCA1 receptor for lactate and lactate intrinsic activity as a HDAC inhibitor in the development of anticancer therapy-resistant tumor phenotype, with special regard to cervical cancer cells. Importantly, the latest study provided new insight into the role of microorganism-mammalian cell interactions in the female genital tract and demonstrated a novel mechanism underlying the efficacy of retroviral transduction through lactate-driven modulation of DNA-PKcs cellular localization. To date, very few studies have focused on mechanisms of lactate-driven enhancement of DNA repair and up-regulation of particular multidrug resistance proteins in cancer cells with respect to their intracellular regulatory mechanisms triggered by lactate. In this review, we summarize the main achievements in the field of lactate impact on cell biology that may promote undesirable alterations in cancer physiology and mitigate retroviral infections.